Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4ra11377b
|View full text |Cite
|
Sign up to set email alerts
|

A convenient method to prepare a novel alkali metal sodium doped carbon nitride photocatalyst with a tunable band structure

Abstract: A novel alkali metal sodium doped carbon nitride photocatalyst with a tunable band gap was prepared using dicyandiamide monomer and sodium hydrate as precursors. X-ray diffraction (XRD), N 2 adsorption, UV-vis spectroscopy, scanning electron microscopy (SEM), photoluminescence (PL) and X-ray photoelectron spectroscopy (XPS) were used to characterize the prepared catalysts. The CB and VB potentials of graphitic carbon nitride could be tuned by controlling the sodium concentration. In addition, sodium doping inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(60 citation statements)
references
References 42 publications
3
55
1
Order By: Relevance
“…Research has shown that doping with metal and non‐metal atoms, such as C, N, O, S, P, I, K, Na, Fe, and Cu, also plays a vital role in promoting the photocatalytic activity of g‐C 3 N 4 . Usually, a dopant energy level is be induced between the energy gap of g‐C 3 N 4 after substitution of C and N with heteroatoms, and this broadens the light‐responsive range and causes higher light efficiency as well as better electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that doping with metal and non‐metal atoms, such as C, N, O, S, P, I, K, Na, Fe, and Cu, also plays a vital role in promoting the photocatalytic activity of g‐C 3 N 4 . Usually, a dopant energy level is be induced between the energy gap of g‐C 3 N 4 after substitution of C and N with heteroatoms, and this broadens the light‐responsive range and causes higher light efficiency as well as better electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that doping with metal and non-metal atoms, such as C, N, O, S, P, I, K, Na, Fe, and Cu, also plays a vital role in promoting the photocatalytic activity of g-C 3 N 4 . [24][25][26][27][28][29][30][31][32][33] Usually,adopant energy level is be induced between the energy gap of g-C 3 N 4 after substitution of Ca nd N with heteroatoms,a nd this broadens the light-responsive range and causes higher light efficiency as well as bettere lectrical conductivity.F or instance, ac alcination-refluxing method was reported for the synthesis of Mn-doped g-C 3 N 4 for the highly efficient photocatalyticd egradation of organic dyes and As an amorphous or semicrystalline material, graphitic carbon nitride (g-C 3 N 4 )d isplays poor photocatalytic activity owing to rapid recombination of the photogenerated chargec arriers, which is mainly caused by ah igh density of defects in the graphitic structure. In this work, ap orous O-doped g-C 3 N 4 (P-CNO) nanosheet with ah ighly ordered architecture is fabricated by introducing an ovel hydrothermal treatment to the precursor before the final thermal condensation.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient utilisation of visible light would enable the exploitation of sunlight as a source of energy, which consists of about 40% visible light. Generally, strategies such as doping the semiconductor with metal ions (alkali, alkaline earth, noble, rare earth, and transition metals) [43][44][45][46][47], non-metal ions (oxygen, sulphur, nitrogen, phosphorus, halogens, carbon, and boron) [48][49][50][51], codoping/multidoping (metal + metal, non-metal + metal, non-metal + non-metal) [52][53][54][55], coupling semiconductors with carbon nanomaterials (reduce graphene oxide (RGO), graphene oxide (GO), multiwalled carbon nanotubes (MWCNTs), single-walled carbon nanotubes (SWCNTs), carbon nanospheres (CNS), fullerenes, etc.) [56][57][58][59], sensitisation (dye, polymer and surface complex sensitisation) [60][61][62], and coupling two or more semiconductors [63][64][65] have been extensively investigated for improving the photocatalytic activity of various semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Li + , Na + , K + and among other alkali-metal ions could be incorporated into the g-C3N4 framework, causing spatial charge carrier distribution to be induced in various intercalated areas. [43,124,198] Zhang et al reported an original Na + co-doping with CNx photo-catalyst with an adjustable gap in-between bands was made with dicyandiamide monomer and NaOH as precursors [200].…”
Section: Dopingmentioning
confidence: 99%